Sistem Pendukung Keputusan Penentuan Murid Terbaik Dengan Metode Waspas - Aggry Saputra; Ziko Mustagfir (Jurnal Bangkit Indonesia, 2021)
Decision Support Systems are basically made to facilitate decision making so that subjective decision making does not occur. At SMAN3 Kundur, the best student decision-making process is made using WASPAS which consists of several criteria, namely the value of student activity, the value of attitudes, the average value of report cards, the value of academic and non-academic achievements. In building this system the author uses the development method using the Weighted Aggregated Sum Product Assessment (WASPAS) method, and for the system design the author uses the Unified Modeling Language (UML). For the manufacture of information systems using the MySQL database. The result of this research is a decision support information system using the Weighted Aggregated Sum Product Assessment (WASPAS) method. , because it is processed by the system